1979
DOI: 10.1029/jb084ib08p04011
|View full text |Cite
|
Sign up to set email alerts
|

Geos 3 wave height measurements: An assessment during high sea state conditions in the North Atlantic

Abstract: During February 1976 a concentrated effort was made to monitor the sea state in the North Atlantic Ocean using Geos 3 radar altimeter wave form data and specialized data processing techniques. The average wave form was computed and fitted in a least squares sense by an error function whose slope is directly relatable to the ocean's significant wave height. The resulting measurements were compared with various sets of truth data. Underflights of Geos 3 orbits were made by a NASA C‐54 aircraft equipped with two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1979
1979
1999
1999

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…For an altimeter developed by the AAFE program, the mean difference was 0,62 meters and the standard deviation Quasi-synoptic wave height fields were prepared for the North Atlantic ocean using the GEOS-3 data. 44 At the same time, the initial value specifications for the wave heights, as given by the Spacecraft Meteorology Group, the FNOC SOWE model, and the National Meteorological Center were obtained.…”
Section: Verification Of Significant Wave Heights By Means Of Wave Hementioning
confidence: 99%
“…For an altimeter developed by the AAFE program, the mean difference was 0,62 meters and the standard deviation Quasi-synoptic wave height fields were prepared for the North Atlantic ocean using the GEOS-3 data. 44 At the same time, the initial value specifications for the wave heights, as given by the Spacecraft Meteorology Group, the FNOC SOWE model, and the National Meteorological Center were obtained.…”
Section: Verification Of Significant Wave Heights By Means Of Wave Hementioning
confidence: 99%
“…Therefore, by processing the return pulse data, we can get not only the r.m.s. wave height (Parsons 1979)) but also other statistical properties such as the skewness of the surface wave elevation distribution. This coupled with the results by Huang & Long (1980) which showed that one can actually get the § and no (calculated from A,) from the altimeter data.…”
Section: An Application Of the Wallops Spectrummentioning
confidence: 99%
“…The wind speeds and the wave heights globally observed by an altimeter are considered to be useful as data for validation of various models of the atmosphere and the oceans such as wave forecasting [e.g., Parsons, 1979;Queffelou, 1983], or as inputs to atmosphere and ocean circulation models. However, the temporal frequency of observation by the Geosat altimeter is coarse for detailed study of the physical processes of wind wave development with time, although the spatial distributions of wind and waves observed along the ground tracks are very important snapshots of the wind and wave field, which are difficult to take from other platforms such as vessels, buoys, and towers.…”
Section: Introductionmentioning
confidence: 99%